Introduction (translation. a transdisciplinary journal, 2022)
Dear Reader,I am glad and proud to present translation's third issue: it is growing, we are surviving despite several difficulties, and we areable to present a varied content that continues to explore the many different aspects of the phenomena of translation. Both our readership and authorship are increasing, and we are continuing to accomplish our ambition of being transdisciplinary.